Palynology and Paleobotany of Permo-Triassic Beacon Supergroup at Allan Hills, South Victoria Land, Antarctica: stratigraphical and paleoenvironmental change implications - Corti Valentina (Università degli Studi di Siena, 2021)
Nowadays the Antarctic continent is almost entirely covered by ice (around 98% of the total land surface) and the conditions are inhospitable for vegetation, apart from very few species such as mosses and lichens. During the geological time however, conditions were very different and the Phanerozoic fossil record documents several occurrences of vegetation remains also indicating the presence of wide high latitude forests. The life of plants in the continent was obviously strictly influenced by the evolving paleogeography and paleoenvironmental conditions and their mutual interactions during each time age of vegetation record. The thesis project has been finalized to define, constrain and discuss with new field and laboratory data the most likely Late Permian and Triassic paleoenvironmental reconstructions for the Victoria Land region in Antarctica, on the basis of a new set of paleobotany and palynological investigations of the unique fossiliferous strata recently found in the Beacon Supergroup of Allan Hills (South Victoria Land). The study was developed following a broad multidisciplinary and multi-analytical methodology in which paleobotany (including innovative approaches), palynology and palynostratigraphy methods and techniques play a key role in the reconstruction of the paleoenvironmental conditions and their changes through the time. In the palynostratigraphic sequence of Allan Hills were recovered the EPE, a strata horizon with long-shaped inertinite probably referred to a paleo-fire, situated in the last level of coal of the Permian sequence; going up in the sequence the paleoflora is affected by deeply change, as an adaptation to the new environmental condition up to the PTB, were the major samples were completely inert, due to a poor presence of flora and a changing of the sedimentary condition. After the PTB the first palynomorphs recovered are associated to an intensive fungal and algae activity, and just at the end of the Early Triassic, the flora came back to be flourishing, even if with a ...